Pengembangan Aplikasi Pemindaian Kode Pengujian Unit (Studi Kasus: PT Global Digital Niaga) - Ade Wija Nugraha; Bayu Priyambadha; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Unit testing is one phase in the software testing process, but there are still some programmers who are reluctant to do the unit testing. These problems also occur in PT. Global Digital Niaga. Some programmers don't pay attention to the quality of the unit testing's code and only pay attention to the value of the unit testing code coverage. Researchers develop applications that can be used to scan unit testing codes and identify the incorrect unit testing code based on rules. The scanning process starts with searching for information on the uploaded project. Then, application scans production code and unit testing code using JavaParser library. After that, the application analyzes each scanned unit test code whether the code matches with writing rules or not. Then, the application saves the scan results and displays them. The first phase of this research is the study of literature. Then, the requirements engineering produced 25 functional and 2 non-functional. Next is the design and followed by the implementation by creating a website application. After that, the testing with a 100% pass, 100% valid, and 100% accurate for unit, validation, and accuracy testing. The application can run on eight different browsers for compatibility testing.